OsNAR2.1 induced endogenous nitrogen concentration variation affects transcriptional expression of miRNAs in rice - Zhang, Yong; Fan, Xiaoru; Wang, Yulong; Kong, Pulin; Zhao, Ling; Fan, Xiaorong; Zhang, Yadong (Frontiers in Plant Science, 2023)
The studies of rice nitrogen concentration on the expression of miRNA so far are mostly limited to the exogenous nitrogen, leaving the effect of endogenous nitrogen largely unexplored. OsNAR2.1 is a high-affinity nitrate transporter partner protein which plays a central role in nitrate absorption and translocation in rice. The expression of OsNAR2.1 could influence the concentration of the endogenous nitrogen in rice. We showed that the expression and production of miRNA in rice can be influenced by manipulating the endogenous nitrogen concentration via OsNAR2.1 transgenic lines. The small RNA content, particularly 24 nucleotides small RNA, expressed differently in two transgenic rice lines (nitrogen efficient line with overexpression of OsNAR2.1 (Ov199), nitrogen-inefficient line with knockdown OsNAR2.1 by RNAi (RNAi)) compared to the wild-type (NP). Comparative hierarchical clustering expression pattern analysis revealed that the expression profiles of mature miRNA in both transgenic lines were different from NP. Several previously unidentified miRNAs were identified to be differentially expressed under different nitrogen concentrations, namely miR1874, miR5150, chr3-36147, chr4-27017 and chr5-21745. In conclusion, our findings suggest that the level of endogenous nitrogen concentration variation by overexpression or knockdown OsNAR2.1 could mediate the expression pattern and intensity of miRNA in rice, which is of high potential to be used in molecular breeding to improve the rice responses towards nitrogen utilization.